Translocality in Global Software Development: the Dark Side of Global Agile. (4th March 2019) - Bjørn, Pernille; Søderberg, Anne-Marie; Krishna, S
Abstract : What happens when agile methods are introduced in global outsourcing set-ups? Agile methods are designed to empower IT developers in decision-making through self-managing collocated teams. We studied how agile methods were introduced into global outsourcing from the Indian IT vendor's perspective. We explored how agile processes in global outsourcing impacts work conditions of the Indian IT developers, and were surprised to find that agile methodologies, even after 3 years of implementation, created a stressful and inflexible work environment negatively impacting their personal lives. Many of the negative aspects of work, which agile methodologies were developed to reduce, were evident in the global agile outsourcing set-up. We propose translocality to repudiate the dichotomy of global/local reminding us that methodologies and technologies must be understood as immediately localized and situated. Translocality helps us to explain why we cannot determine the impact of global agile as a methodology independent of how it unfolds at particular sites. Instead, we must attend to concrete practices of use when evaluating the impact of new methods.